2016
DOI: 10.20463/jenb.2016.12.20.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Red ginseng as an ergogenic aid: A systematic review of clinical trials

Abstract: An ergogenic aid can be defined as an equipment, technique, and substance used for enhancing sports performance. Ergogenic aids can be classified into different forms such as nutritional, pharmacological, and physiological aids. They range from use of accepted techniques such as high altitude training to consumption of illegal substances such as steroid. The efficacy of many of these is controversial, whereas the side effects are evident. An herb is a plant or plant part used for its scent, flavor, or therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…The mechanism by which PG improve endurance performance might apparently include its ability in enhancing creatine synthesis within the body, influencing carbohydrate and lipid metabolism, anabolic functions such as synthesis of DNA, RNA and proteins, possessing biological active properties like adaptogenic, anti-stress, anti-fatigue, anti-hypertensive and antioxidant, vasodilation, bradycardia, as well as efficacy in improved psychomotor performance. [3,31] From the discussion of this study, it could be postulated that the active ingredients in PG were sufficiently absorbed during the trials to elicit positive effects among recreational runners. There were differences in opinions among different studies, which might be due to difference in study design of those studies, lack of availability of…”
Section: Estimation Of Catalasementioning
confidence: 90%
See 1 more Smart Citation
“…The mechanism by which PG improve endurance performance might apparently include its ability in enhancing creatine synthesis within the body, influencing carbohydrate and lipid metabolism, anabolic functions such as synthesis of DNA, RNA and proteins, possessing biological active properties like adaptogenic, anti-stress, anti-fatigue, anti-hypertensive and antioxidant, vasodilation, bradycardia, as well as efficacy in improved psychomotor performance. [3,31] From the discussion of this study, it could be postulated that the active ingredients in PG were sufficiently absorbed during the trials to elicit positive effects among recreational runners. There were differences in opinions among different studies, which might be due to difference in study design of those studies, lack of availability of…”
Section: Estimation Of Catalasementioning
confidence: 90%
“…Previous studies also suggested that PG showed a beneficial role on fuel homeostasis by sparing muscle glycogen, promoting FFA oxidation (lipolysis) and inhibiting lipogenesis during endurance exercise, thus enhancing exercise performance. [31] Exercise induced oxidative stress was estimated by serum levels of LPO, SOD, catalase and total thiol. In this study, serum level of LPO decreased significantly (p<0.05) in PG than PL trial, thereby reducing the lipid peroxidation of cells whereas the levels of antioxidant enzymes (SOD, catalase and total-thiol) were found to be increased significantly (p<0.05) in PG than PL trial for combating with this exercise induced oxidative stress.…”
Section: Estimation Of Catalasementioning
confidence: 99%
“…Ginseng is used to promote rejuvenation and longevity, for frailty and stress, weakness and fatigue, both mental and physical (Ogawa‐Ochiai & Kawasaki, ), and as supportive treatment for diabetes, cardiovascular disease and many others (Mancuso & Santangelo, ). Recently, a number of systematic reviews have critically evaluated the clinical evidence for and against the effectiveness of ginseng in a number of conditions, such as erectile dysfunction (Borrelli, Colalto, Delfino, Iriti, & Izzo, ), chronic fatigue (Arring, Millstine, Marks, & Nail, ), hypertension (Lee, Lim, Jun, Choi, & Lee, ), diabetes (Gui, Xu, Xu, & Yang, ), Alzheimer's disease (Wang et al, ) and as an ergogenic aid (Lee, Jung, & Lee, ).…”
Section: Ginseng‐targeted Extractsmentioning
confidence: 99%
“…Ergogenic is defined as the equipment, techniques and substances used to enhance sports performance. Ergogenic aids are classified into various forms, such as nutritional, pharmacological and physiological aids [1]. Ergogenic also means tonic which is an ingredient used to increase stamina, endurance, and to minimize fatigue [2].…”
Section: Introductionmentioning
confidence: 99%